2020
DOI: 10.3390/en13236350
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Grids for the Sustainable Electrification of Rural Areas in Sub-Saharan Africa: Assessing the Potential of KeyMaker Models

Abstract: Solar hybrid mini-grid systems possess the potential to substantially support electrification in sub-Saharan Africa. While their technical reliability has been proven, their financial viability is achieved only by heavy subsidization as of now. Due to the growing importance of results-based financing, we ask whether newly developed business models leveraging on the value added of electricity supply in rural areas (such as the KeyMaker Model) bare the potential to substantially reduce amount of grants required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…-micro-and mini-grids provide first-time electricity access in previously unconnected areas [89]; -warm electrification refers to the practice of connecting individual solar power systems to create low-voltage micro-grids [90]; -for example, efficient use of electricity in the workplace [11]; -seeds of electrification, whereby prosumers replace diesel use by selling excess electricity to nearby homes and businesses [91]; -energy cost savings, decarbonization of distributed generation, and innovative financing for prosumer business models are the three primary value propositions for decarbonizing the grid [19]; -energy efficiency and digitalization, for instance, can lead to the creation of virtual power plants for prosumers, which can then be used for energy management and to generate income [92]; -battery storage for electricity in conjunction with micro-and mini-grids to meet peak demand or store energy produced locally [93].…”
Section: Energy Product Service System To Customersmentioning
confidence: 99%
See 3 more Smart Citations
“…-micro-and mini-grids provide first-time electricity access in previously unconnected areas [89]; -warm electrification refers to the practice of connecting individual solar power systems to create low-voltage micro-grids [90]; -for example, efficient use of electricity in the workplace [11]; -seeds of electrification, whereby prosumers replace diesel use by selling excess electricity to nearby homes and businesses [91]; -energy cost savings, decarbonization of distributed generation, and innovative financing for prosumer business models are the three primary value propositions for decarbonizing the grid [19]; -energy efficiency and digitalization, for instance, can lead to the creation of virtual power plants for prosumers, which can then be used for energy management and to generate income [92]; -battery storage for electricity in conjunction with micro-and mini-grids to meet peak demand or store energy produced locally [93].…”
Section: Energy Product Service System To Customersmentioning
confidence: 99%
“…To compensate, they are willing to pay more for electricity generated by conventional means [87]. There is evidence that productive electricity use can boost rural economies, albeit to varying degrees [11]. Several studies have found that users are more receptive to value propositions when they include promises of increased household income from sources like energy crop cultivation, employment in bioenergy supply chains, and improved living conditions [109][110][111].…”
Section: Social Long-term Viabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there is a lack of knowledge about potential revenue from non-electricity sales, and income from complementary services is more diverse and poorly documented [39]. Research is needed to assess synergies between BMs and sectors, such as agriculture value chains and applications [40]. Developers document their innovations' learning outcomes, but they do not share them with actors outside their organization.…”
Section: F2 F3-knowledge Development and Knowledge Diffusionmentioning
confidence: 99%